2011
DOI: 10.1155/2011/328054
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Markers for PTSD Risk and Resilience Among Survivors of the World Trade Center Attacks

Abstract: Abstract.We have previously reported the differential expression of 17 probe sets in survivors of the 9/11 attacks with current posttraumatic stress disorder (PTSD) compared to similarly exposed survivors with no lifetime PTSD. The current study presents an expanded analysis of these subjects, including genotype at FKBP5, a modulator of glucocorticoid receptor (GR) sensitivity. It includes data from additional subjects who developed PTSD following 9/11 but then recovered, distinguishing expression profiles ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 9 publications
3
90
0
2
Order By: Relevance
“…'PTSD-responsive' mice also show less overall transcriptional change in response to stress compared with 'PTSD-resilient' mice (Lebow et al, 2012), suggesting that enduring anxiety after trauma may be in part related to attenuated adaptation of stress systems. The present study also observed that males, but not females, exposed to CRHOE dev or stress exhibited reduced cortical expression of Fkbp51, a protein that curbs excess glucocorticoid signaling and modulates the association between early-life stress and PTSD (Binder, 2009;Yehuda et al, 2009;Sarapas et al, 2011;Yehuda et al, 2009). Recent prospective studies indicate that reduced Fkbp5 expression before trauma is a risk factor for the development of PTSD (van Zuiden et al, 2012).…”
Section: Discussionsupporting
confidence: 74%
“…'PTSD-responsive' mice also show less overall transcriptional change in response to stress compared with 'PTSD-resilient' mice (Lebow et al, 2012), suggesting that enduring anxiety after trauma may be in part related to attenuated adaptation of stress systems. The present study also observed that males, but not females, exposed to CRHOE dev or stress exhibited reduced cortical expression of Fkbp51, a protein that curbs excess glucocorticoid signaling and modulates the association between early-life stress and PTSD (Binder, 2009;Yehuda et al, 2009;Sarapas et al, 2011;Yehuda et al, 2009). Recent prospective studies indicate that reduced Fkbp5 expression before trauma is a risk factor for the development of PTSD (van Zuiden et al, 2012).…”
Section: Discussionsupporting
confidence: 74%
“…These include polymorphisms or expression of BDNF (Krishnan et al, 2007), GABRA2 (Nelson et al, 2009), 5-HT1A receptors, dopamine or serotonin transporters (Segman et al, 2002;Kilpatrick et al, 2007;Stein et al, 2009;Wald et al, 2013), catechol-O-methyl transferase (COMT; Jabbi et al, 2007;Kolassa et al, 2010), glucocorticoid receptors and factors that modulate them such as FK506-binding protein (FKBP5;Binder et al, 2008;Derijk and de Kloet, 2008;McGowan et al, 2009;Sarapas et al, 2011), and methylation of corticotrophin-releasing factor (CRF) receptor DNA (Elliott et al, 2010). Several genetically distinct rodent lines are differentially resistant/vulnerable to the effects of stress (Razzoli et al, 2011;Savignac et al, 2011;Camp et al, 2012;Fuchsl et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the transcriptional patterns of expression for genes involved in inflammatory pathways have also been associated with PTSD (Segman et al, 2005;Yehuda et al, 2009;Zieker et al, 2007). Nuclear factor-κB (NFκB), signal transducer and activator of transcription 5B, and nuclear factor I/A are all critical transcription factors with substantive roles in the activation of cytokine responses to challenge whose activity is increased in the presence of PTSD (Guardado et al, 2016;O'Donovan et al, 2011;Pace et al, 2012;Sarapas et al, 2011). Gene expression of the proinflammatory cytokine IL-18 and its receptor IL-18R1 is decreased in individuals with PTSD (Mehta et al, 2011;Segman et al, 2005;Zieker et al, 2007).…”
Section: Ptsd and Inflammationmentioning
confidence: 99%